2023
DOI: 10.1093/jnci/djad065
|View full text |Cite
|
Sign up to set email alerts
|

Clonal hematopoiesis in older patients with breast cancer receiving chemotherapy

Abstract: Background The expansion of hematopoietic stem cells carrying recurrent somatic mutations, termed clonal hematopoiesis (CH), is common in elderly individuals and associated with increased risk of myeloid malignancy and all-cause mortality. Though chemotherapy is a known risk factor for developing CH, how myelosuppressive therapies affect the short-term dynamics of CH remains incompletely understood. Most studies have been limited by retrospective design, heterogeneous patient populations, var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In this study, we have shown that the strong selective pressure to overcome impaired ribosome biogenesis and avoid p53-mediated cell death in SDS results in convergent somatic mutations in a unique set of target genes, not observed in the context of ageing 45 47 or haematological perturbations such as autoimmunity 48 or chemotherapy 49 . The survival advantage conferred by such mutations results in HSC clonal expansions, often commencing very early in life, even in utero, in individuals with SDS.…”
Section: Discussionmentioning
confidence: 90%
“…In this study, we have shown that the strong selective pressure to overcome impaired ribosome biogenesis and avoid p53-mediated cell death in SDS results in convergent somatic mutations in a unique set of target genes, not observed in the context of ageing 45 47 or haematological perturbations such as autoimmunity 48 or chemotherapy 49 . The survival advantage conferred by such mutations results in HSC clonal expansions, often commencing very early in life, even in utero, in individuals with SDS.…”
Section: Discussionmentioning
confidence: 90%
“…Interpretation of ctDNA results requires careful consideration especially regarding non‐tumour mutations that may occur in CHIP. These mutations can overlap with common somatic alterations, 100 thus filtering out CHIP‐associated genes is important, particularly for genes such as ATM , BRCA1/2 , TP53 , and PTEN 101 . In terms of gene fusion analyses, ctDNA‐based assays have proven essential in complementing tissue testing 102 .…”
Section: Integration Of Tissue and Ctdna Testingmentioning
confidence: 99%